Responsivitas Ulama terhadap Pernikahan Beda Agama Perspektif Mufassir Al-Qur'an dan Hukum Perkawinan di Indonesia - Kurniawan, Rifa'i; Arif, Mohammad; Khulwani (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Interfaith marriage is a complex and often controversial topic in Islamic law and social dynamics, especially in Indonesia which has high religious diversity. This study aims to evaluate the views of Qur'anic commentators and the responses of Muslim scholars on interfaith marriage and its relevance to marriage law in Indonesia. The approach used is qualitative, using library research to analyze various Qur'anic interpretations from classical and contemporary commentators, and evaluating the views of Muslim scholars on the legitimacy and challenges of interfaith marriage. From the literature studied, there are various interpretations among commentators, ranging from very strict to more flexible, depending on their respective historical and social contexts. Some support the adjustment of Islamic law to better reflect the increasingly pluralistic social reality. This study emphasizes the importance of ongoing dialogue between religious texts and social reality, in accordance with the spirit of marriage law in Indonesia. With increased awareness and understanding, it is hoped that society will be more accepting and respectful of differences, thereby creating better social harmony. In conclusion, the difference in interfaith marriage is centered on the People of the Book, for textual thinkers who only focus on one verse, this is the face of thoughts that consider it unfinished, namely the letter Al-Maidah: 5. While the majority of scholars conduct research with various approaches, both the Qur'an and other rules, so that their conclusion decides that it is not permissible. With more objective and methodological reasons.